Clinical management of endo-perio lesion through guided tissue regeneration : a 5 year follow-up = Manejo clínico de una lesión endo-perio a través de la regeneración tisular guiada : control post-operatorio de 5 años - Mukhtar, Munis
Progressive periodontal disease causes loss of supporting structures of teeth resulting in deep bony defects. In this case a report of 22-year old female patient is being presented with clinical findings of vertical bone loss in two adjacent teeth, on distal surface of 2nd upper right premolar and mesial surface of upper right 1st molar. Root canal treatment, non-surgical periodontal therapy followed by guided tissue regeneration was carried out using decalcified freeze-dried bone allograft (DFDBA) and collagen membrane. Analysis of clinical and radiographic findings showed marked reduction in pocket depth up to 12mm with hard tissue repair on 3-month, 2-year and 5- year follow ups.